Pengendalian Persediaan Semen dengan Metode Min Max pada PT. Bukaka Teknik Utama - Nurulinzany; Ahmad Sawal; Muh. Ikhsan (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
PT. Bukaka Teknik Utama is a company engaged in the construction and manufacturing sectors. One of its ongoing projects is the construction development project of PT. Bumi Mineral Sulawesi. The problem faced by the company is the shortage of cement inventory due to inventory control practices that rely solely on estimations without proper planning. This condition caused the construction process to come to a complete halt in October, November, and December because the cement demand from construction workers could not be fulfilled, resulting in potential losses as the company's operational activities were entirely suspended. This study employed a prescriptive research design with a quantitative approach. The research analyzed data by describing the existing inventory control practices implemented by the company based on collected data. The objective of this study was to optimize cement inventory control at PT. Bukaka Teknik Utama in the construction project of PT. Bumi Mineral Sulawesi using the Min-Max Stock method. The results of the analysis using the Min-Max Stock method showed that the optimal inventory parameters consisted of a safety stock of 240 bags, a minimum inventory level of 332 bags, a maximum inventory level of 424 bags, an order quantity of 185 bags, a reorder point of 332 bags, and an ordering frequency of 30 orders. These results indicate that cement inventory can be effectively controlled through the implementation of the Min-Max Stock method, thereby reducing the risk of stock shortages and supporting the continuity of construction activities